An assessment of the creation of a Filipino-Operated Web Map - Calma, Sean Christian (Technology Management Center, 2007)
In this paper, search engines and web applications will be described. Its usage and functions will also be explained. The more popular search engines and web map applications will be identified. Google, Microsoft and Yahoo are racing to transform web maps into full-blown browsers, organizing information-and advertisements-according to geography. The methodology used in formulating the forecast is described in this paper, Analyzing strengths, weaknesses, opportunities and threats of the political, economic, socio-cultural and technological factors of search engines will help forecast the growth of web maps in the Philippines. Appropriate figures and statistics were presented to aid in the analysis. There are two recommendations presented for in creating a Filipino-operated web application. The advantages and disadvantages of each option have been identified.